"REFUGEE ENTREPRENEURSHIP" IN THE CONTEXT OF ENTREPRENEURSHIP DEVELOPMENT IN THE DOMESTIC TOURISM INDUSTRY (Development Service Industry Management, 2024)
The beginning of the second decade of the XXI century was marked by a significant increase in the number of forced migrants and refugees all over the world. Conflicts, political instability, economic crises and natural disasters have forced millions of people to leave their homes in search of safety and a better life. A special place in this context is occupied by the experience of the countries of the European Union (hereinafter referred to as the EU), which faced a large-scale migration crisis, especially after 2015, when a significant number of refugees from the Middle East and North Africa began to arrive en masse in Europe. EU countries faced unprecedented challenges related to the reception, accommodation and integration of refugees and internally displaced persons. These challenges include issues of security, social inclusion, access to the labor market, health and education.The purpose of the study is to systematize the international experience of "refugee entrepreneurship", as well as to develop recommendations for the development of tools to stimulate entrepreneurship of forcibly displaced persons in Ukraine.According to the International Organization for Migration, in 2023, about 15% of IDPs (approximately 745,000 people) do not plan to move, but seek to integrate at their current place of residence as a long-term solution. The results of the survey of IDPs regarding the list of needs for successful integration in a new environment are meaningful: in particular, the most mentioned integration need in the entire sub-sample was financial support (56%), a third of displaced men also expressed the need to increase their own opportunities to provide income (for example, through vocational training ).An important condition is the creation of a favorable environment for their integration, including access to the labor market, education and health services, as well as support in entrepreneurship and cultural adaptation. Therefore, in many countries of the world, appropriate international programs to support entrepreneurship among immigrants have been developed.
Keywords: tourism; tourism entrepreneurship; integration; internally displaced persons; refugees